Początki są zawsze trudne? O dzieciństwie, polityce i filozofii - Weber, Barbara (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Humans are mainly rational beings and children seem to be “defective creatures”. In contrast to that popular and reduced concept of childhood, thinkers like Kant, Arendt and Lévinas explored the more complex anthropological concept of child in its Otherness. They regard childhood as a necessary aspect of the society. Kant in his essay What Does it Mean to Orient Oneself in Thinking? calls for the early encouragement of reason.